PENGARUH KARAKTERISTIK INDIVIDU, PENGALMAN KEREJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KANTOR BALAI BESAR KARANTINA PERTANIAN SURABAYA - jurnalmap map; Mohammad Samsul Hedar (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
This research was conducted at the Office of the Surabaya Agricultural Quarantine Center with a population of 286 people, the number of research samples was 166 people. The research objective is to describe and determine whether individual characteristics, work experience, work environment have an influence either simultaneously or partially on the performance of the employees of the Surabaya Agricultural Quarantine Office. Furthermore, to determine which variables among individual characteristics, work experience, work environment have a dominant influence on the performance of the employees of the Surabaya Agricultural Quarantine Office. This type of research used in this research is explanatory research. The approach in this research uses a quantitative approach. The results show that simultaneously, individual characteristics, work experience and work environment have a significant influence on employee performance. Partially, individual characteristics, work experience and work environment have a significant influence on employee performance and work experience has a dominant influence on employee performance. Keywords: individual characteristics, work experience, work environment, employee performance